(3GQJTGa GdVQH ef dSGf GdYQHs - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf,J (B745 (3g` s
(3ChdgG (B:s
(3hHYO, aEf Yde GdfMh UYH GdeQGe, eSJYUj Ydi GdCagGe dG jfaP aj eYQaJg EdG GdPgf GdSdje s
(3BNQgG (B:s
(3hGdae HGdeje eVGakG fMh bhdg(B: (3Y(B: (3jUHM XeBf haj GdHMQ ageg GSJYeGdg HGdhGh hGdCda hGdjGA YfO CHj Ydj s
(3GfXQ GdLRA GdChd (B7 (3fMhs
(3fSNI ofbdJ ef fSNI efbhdI ef fSNI HNW GdeDdas
(3hocJHJ HYV CdaGXgG HGdMeQI hebSeI aj GdOGNd Edi CLRGA hHBNQ cd LRA agQS dgs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdfMhs